'Axis of evil' haunts Bush - Abd Razak, Dzulkifli (2007)
A SOMEWHAT subdued George W. Bush delivered his sixth State of the Union address last week. It is in some ways significant as Bush is a lame duck (Republican) president facing for the first time a Democratic Congress in 12 years. No doubt, it is among the toughest yet since the days of Richard Nixon in 1974, what with Senator Hillary Clinton’s welltimed announcement about her interest in the 2008 presidential race. All said and done, it could not match the arrogance with which he delivered the 2002 address, five years ago, on Jan 29, 2002. It was then that the term "axis of evil" was introduced to describe countries accused of sponsoring what he called "terrorism".